2015
DOI: 10.1609/aaai.v29i1.9670
|View full text |Cite
|
Sign up to set email alerts
|

This Time the Robot Settles for a Cost: A Quantitative Approach to Temporal Logic Planning with Partial Satisfaction

Abstract: The specification of complex motion goals through temporal logics is increasingly favored in robotics to narrow the gap between task and motion planning. A major limiting factor of such logics, however, is their Boolean satisfaction condition. To relax this limitation, we introduce a method for quantifying the satisfaction of co-safe linear temporal logic specifications, and propose a planner that uses this method to synthesize robot trajectories with the optimal satisfaction value. The method assigns costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Then, the user-defined priority list is used to synthesize the least-violating strategy. Similarly, the work in [45] employs user-defined costs to define a distance to satisfaction of co-safe LTL specifications. The costs in that work, however, are over propositions, and the authors introduce a method of constructing a weighted automoton and generating a robot plan with the least distance to satisfaction.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Then, the user-defined priority list is used to synthesize the least-violating strategy. Similarly, the work in [45] employs user-defined costs to define a distance to satisfaction of co-safe LTL specifications. The costs in that work, however, are over propositions, and the authors introduce a method of constructing a weighted automoton and generating a robot plan with the least distance to satisfaction.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…A salient feature of our algorithm is that the complexity to solve the final product game is primarily governed by the temporal goal and not the satisficing goal. What we mean is that if the temporal goal is given by a fragment of LTL, such as co-safe LTL (Lahijanian et al 2015), then the final product game would be reachability game. This is because co-safe LTL formulas are represented by co-safety automata and thus their combination with comparators would also be a co-safety automata.…”
Section: Satisficing and Temporal Goalsmentioning
confidence: 99%
“…This feature has implications on the practicality of our algorithm. In practice, it has been observed that wide-ranging temporal goals in robotics domains can be expressed in simpler fragments and variants of LTL, such as co-safe LTL (Lahijanian et al 2015) and LTLf (He et al 2017). These fragments can be expressed as conjunctions of safety and reachability goals.…”
Section: Satisficing and Temporal Goalsmentioning
confidence: 99%
“…Early work on planning with linear temporal logic (LTL) specifications in MDPs includes that of Ding et al (2011), who employ dynamic programming to construct a policy which almost surely satisfies an LTL specification. Subsequent work has considered how to plan with LTL specifications that are only partially satisfiable (Lacerda, Parker, and Hawes 2015;Lahijanian et al 2015), and how to work with multiple specifications which may not all be satisfiable (Tumova et al 2013;Kasenberg and Scheutz 2018) or represented as beliefs over formulas (Shah, Li, and Shah 2019). The present work builds on these latter approaches, describing how an agent planning with multiple specifications in LTL may answer questions about its behavior, including "why" questions.…”
Section: Related Workmentioning
confidence: 99%